Comparative effects of diet supplementation with l-carnitine and dl-carnitine on ammonia toxicity and hepatic metabolism in rats - Gazola Vilma A F G; Lopes Gisele; Dias Rose M M; Curi Rui; Bazotte Roberto B (Acta Pharmacologica Sinica, 2016)
Aim: To compare the effects of chronic supplementation with l-carnitine (LCT) and dl-carnitine (DLC) on ammonia toxicity and hepatic metabolism. Methods: Three groups of male adult rats were studied: 1) supplemented with LCT (1.2 mmol . kg-1 . d-1), 2) supplemented with DLC (1.2 mmol . kg-1. d-1), and 3) control group (COG) not supplemented. Results: The treatment with LCT decreased the toxicity to ammonia. However, the supplementation with DLC did not show any significant effect. In contrast, the effects of the supplementation with LCT and DLC on hepatic metabolism were quite similar, ie, both groups showed: (a) intensified ammonia uptake and decreased urea production from ammonia; (b) increased glucose and urea production from L-glutamine (5 mmol/L). Conclusion: The results suggested that LCT supplementation might protect against ammonia toxicity by extra-hepatic mechanisms.